A NEW SPECIES OF XANTHOSTEMON (MYRTACEAE) FROM NATUNA ISLANDS, INDONESIA - Agung Sedayu (Reinwardtia, 2009)
SEDAYU, A. 2009. A new species of Xanthostemon (Myrtaceae) from Natuna Islands, Indonesia. Reinwardtia 12(5): 447–449. — A new species of Xanthostemon, X. natunae was collected from Natuna Islands,Indonesia, outside the previous known westernmost distribution limit in Palawan (X. speciosus). Its differences with X. confertiflorus Merr. (Celebes) are discussed.